The Educational Reform in the Late Qing Dynasty - Piyasirikul, Kampol (Journal of Sinology (วารสารจีนวิทยา), 2011)
Since the second half of the nineteenth century, China has begun reforming the country in many areas on several occasions. The motivation for these movements was the invasion of Western powers. Among these areas of changes, educational reform was one of the reform policies that the Qing Dynasty Administration has significantly valued over those years. This article studies some crucial educational reforms that occurred between the time Imperial Foreign Studies College was founded in 1862 and when the Imperial Civil Examination System was cancelled, as well as when the Ministry of Education was established in 1905. This article emphasizes the examination of a great number of primary historical documents, while focusing on the main points about the educational reform in the late Qing Dynasty, the main concept of the educational reform, power groups in the administration, progressions and obstructions of the reform, and so on.